Water Quality And Chemical Mass Balance Of Tropical Freshwater Wetlands, Beriah Swamp, Perak - Ismail, Wan Ruslan; Siow, A. Y.; Ali, Ahyaudin (Penerbit UTM Press, 2005)

(untitled)
A Chemical Mass Balance Study Was Conducted In Beriah Swamps, A Tropical Fresh Water Swamp In North Perak, Malaysia From June To October 1998, Aimed At Investigating The Role And Function Of Wetlands In Filtering Sediment And Retaining Sediment And/Or Nutrient. The Flux Of Nutrient And Sediment From Two Input Streams (Beriah Kanan And Beriah Kiri) Were Compared With The Output (Beriah). A Fortnightly And An Intensive Hourly Sampling On The 10-11th October 1998 For 48 Hours, During High Water Conditions Were Carried Out. Results Showed No Significant Difference (P>0.05) In Concentrations Of Almost All Parameters Except For SRP Between Two Input Rivers, But Were Significant Different (P<0.05) Between Inputs And Output During The Fortnightly Sampling. A Very Marked Difference Was Observed During The Intensive Sampling, Indicating An Increase In Phosphate Concentration Coming From The Swamp. Generally, Nutrients And Suspended Sediment Are Trapped In The Swamp, Showing The Efficient Role Of The Wetland As A Nutrient And Sediment Trap. Based On This Limited Sampling, The Retentions For Nitrate, Phosphate, TSS And TDS Were 81, 58, 23 And 42%, Respectively.